Forest zone and root compartments outweigh long-term nutrient enrichment in structuring arid mangrove root microbiomes - Hsiao, Valerie; Erazo, Natalia G.; Reef, Ruth; Lovelock, Catherine; Bowman, Jeff (Frontiers in Forests and Global Change, 2024)
Mangroves offer many important ecosystem services including carbon sequestration, serving as nursery grounds to many organisms, and acting as barriers where land and sea converge. Mangroves exhibit environmental flexibility and resilience and frequently occur in nutrient-limited systems. Despite existing research on mangrove microbiomes, the effects of nutrient additions on microbial community structure, composition, and function in intertidal and landward zones of mangrove ecosystems remain unclear. We utilized a long-term nutrient amendment study in Exmouth Gulf, Western Australia conducted in two zones, the intertidal fringe and supralittoral scrub forests, dominated by Avicennia marina. Root samples were fractionated into rhizosphere, rhizoplane and endosphere compartments and analyzed by 16S rRNA gene amplicon sequencing to determine the effects of nutrient stress on community structure and function. Our data showed species richness and evenness were significantly higher in the scrub forest zone. PERMANOVA analysis revealed a significant effect of nutrient enrichment on beta diversity (p = 0.022, R 2 = 0.012) in the fringe forest zone only. Cylindrospermopsis, which has been associated with harmful algal blooms, was found to be significantly enriched in fringe phosphate-fertilized plots and nitrogen-fixing Hyphomicrobiales were significantly depleted in the scrub nitrogen-fertilized plots. Meanwhile, root compartments and forest zone had a greater effect on beta diversity (p = 0.001, R 2 = 0.186; p = 0.001, R 2 = 0.055, respectively) with a significant interaction between forest zone and root compartment (p = 0.001, R 2 = 0.025). This interaction was further observed in the distinct divergence identified in degradative processes of the rhizosphere compartment between the two forest zones. Degradation of aromatic compounds were significantly enriched in the fringe rhizosphere, in contrast to the scrub rhizosphere, where degradation of carbohydrates was most significant. Our results indicate that nutrient enrichment impacts microbial community structure and function, potentially compromising overall mangrove health and ecosystem stability.